2015
DOI: 10.1371/journal.pone.0118946
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Variations in CLCN6 Identified in Patients with Benign Partial Epilepsies in Infancy and/or Febrile Seizures

Abstract: Nucleotide alterations in the gene encoding proline-rich transmembrane protein 2 (PRRT2) have been identified in most patients with benign partial epilepsies in infancy (BPEI)/benign familial infantile epilepsy (BFIE). However, not all patients harbor these PRRT2 mutations, indicating the involvement of genes other than PRRT2. In this study, we performed whole exome sequencing analysis for a large family affected with PRRT2-unrelated BPEI. We identified a non-synonymous single nucleotide variation (SNV) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
(41 reference statements)
0
12
0
Order By: Relevance
“…The role of CLCN6 in epilepsy has been suggested but not confirmed in two other studies4344. Two SNVs in CLCN6 have been identified in patients with benign partial epilepsies in infancy (BPEI) or benign familial infantile epilepsy (BFIE) but the causal role has not been established4344. Because of these observations, we classified this de novo missense variant of CLCN6 (c.533 A>C) as likely pathogenic but with weak evidence.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The role of CLCN6 in epilepsy has been suggested but not confirmed in two other studies4344. Two SNVs in CLCN6 have been identified in patients with benign partial epilepsies in infancy (BPEI) or benign familial infantile epilepsy (BFIE) but the causal role has not been established4344. Because of these observations, we classified this de novo missense variant of CLCN6 (c.533 A>C) as likely pathogenic but with weak evidence.…”
Section: Resultsmentioning
confidence: 88%
“…The Glu178Ala variant is located in one of the transmembrane helix that was likely involved in ion transportation. The role of CLCN6 in epilepsy has been suggested but not confirmed in two other studies4344. Two SNVs in CLCN6 have been identified in patients with benign partial epilepsies in infancy (BPEI) or benign familial infantile epilepsy (BFIE) but the causal role has not been established4344.…”
Section: Resultsmentioning
confidence: 96%
“…ATP6V0D2 , one of the V‐ATPase‐related transcripts, contributed to a high risk of breast cancer, pancreatic cancer and RCC. CLCN6 belongs to a family of the voltage‐dependent chloride channel protein taking part in a multitude of basal cellular processes including intracellular vesicles acidification and transepithelial transport . However, no study has reported the associations of these genes with these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Malfunction of ClC genes results in various diseases such as myotonia, leukodystrophy, hyperaldosteronism and epilepsy in humans (Blanz et al, 2007; Charlet-B. et al, 2002; Fernandes-Rosa et al, 2018; Yamamoto et al, 2015). The causal relationship among ClC malfunction, physiological consequences, and disease manifestations are not fully understood in many cases.…”
Section: Introductionmentioning
confidence: 99%